MOBILE H EALTH TECHNOLOGY: ORGANIZATIONAL, MEDICAL AND PHARMACOEPIDEMIOLOGICAL APPROACHES FOR CSD PREVENTION IN PRE-PRIMARY CARE - N. P. Kirilenko; V. L. Krasnenkov; A. V. Solov'eva; O. M. Korolyova; T. Y. Bucanova; N. N. Il'ina; N. D. Bazhenov (SINAPS LLC, 2019)
Objective: to evaluate the innovative organizational, medical and pharmacoepidemiological approaches for the prevention of circulatory system diseases in pre-primary care using mobile health technologies.Materials and methods: 3,694 people went through preventive consultation (questionnaires, anthropometry, body fat and blood pressure evaluation, electrocardiography, glucose and blood cholesterol) at equipped medical sites in shopping centers and rural health posts.Results. Among the surveyed, there were both healthy people and patients cardiovascular diseases and diabetes mellitus. Behavioral (insufficient consumption of fruits and vegetables, adding more salt without trying food, physical inactivity, smoking and alcohol abuse) and nutritional (obesity, hypertension, hypercholesterolemia and glycaemia) risk factors of chronic noncommunicable diseases were detected that contribute to high mortality from circulatory system diseases in the Tver region. This is associated with low adherence to drug therapy and its lack of efficacy in patients with hypertension, ischemic heart disease and cerebrovascular diseases.Conclusion: to assess the effectiveness of CSD prevention in pre-primary care, it is possible to use mobile medical sites in shopping centers and rural health posts.